2007
DOI: 10.1002/jbm.a.31547
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated calcification in electrically conductive polymer composites comprised of poly(ε‐caprolactone), polyaniline, and bioactive mesoporous silicon

Abstract: In this study the fabrication and characterization of an electrically conductive composite material comprised of poly(epsilon-caprolactone) (PCL), polyaniline (PANi), and bioactive mesoporous silicon (BioSilicon) is discussed. The influence of PANi and silicon on calcium phosphate induction was assessed via ex vitro calcification analyses (by acellular simulated body fluid (SBF) exposure) both with and without electrical bias. Acceleration of calcium phosphate formation is one possible desirable feature of "sm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 32 publications
0
18
0
1
Order By: Relevance
“…As electrically conductive material, PPy and PANi have been widely explored in diverse biological applications [27,[29][30][31][32]. Despite the potential of using electrically conductive polymers to control cell function, it is difficult to fabricate substrates with an appropriate three-dimensional structure from polymers such as PPy and PANi due to their brittleness and rigidity [20,27].…”
Section: Discussionmentioning
confidence: 99%
“…As electrically conductive material, PPy and PANi have been widely explored in diverse biological applications [27,[29][30][31][32]. Despite the potential of using electrically conductive polymers to control cell function, it is difficult to fabricate substrates with an appropriate three-dimensional structure from polymers such as PPy and PANi due to their brittleness and rigidity [20,27].…”
Section: Discussionmentioning
confidence: 99%
“…The inherent nature of neurons is to transmit electrochemical signals throughout the nervous system and, as a result, they are highly influenced by electrical stimuli (Yu et al, 2008b). Previous studies have shown that electrical stimulation is an effective cue in stimulating either the proliferation or differentiation of various cell types McCaig and Zhao, 1997;Sun et al, 2006;Ciombor and Aaron, 1993;Aaron and Ciombor, 1993;Goldman and Pollack, 1996;Dust and Bawornluck, 2006;Shi et al, 2008;Zhao et al,1996Zhao et al, , 1999Yaoita et al,1990;Guimarda et al, 2007;Rivers et al, 2002;Jeong et al, 2008;Whitehead et al, 2007;Ateh et al, 2006;Schmidt et al, 2003;Valentini et al, 1992). In this review we discuss the electrical properties of nerve cells, the most commonly utilized conductive polymers, namely polypyrrole (PPy) and polyaniline (PANI), the principle of electrical stimulation and the application of electrical stimulation through conductive scaffolds to nerve cells.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] Since the discovery of the natural electrical properties of bone, the idea of coupling endogenous and exogenous electrical activity has been introduced as a possible tool to promote bone fracture healing and differentiation of osteoprogenitor cells. [6][7][8][9][10] Mechanical and electrical stimuli have been known for some time to affect the properties and regenerative capacity of skeletal tissues. Extremely low-frequency electric fields significantly affect stem cell populations, by enhancing cell signaling pathways and differentiation.…”
Section: Introductionmentioning
confidence: 99%